2019
DOI: 10.1038/s41598-019-56670-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale CRISPR activation screen uncovers tumor-intrinsic modulators of CD3 bispecific antibody efficacy

Abstract: Bispecific antibodies (bsAb) that bridge tumor cells and CD3-positive effector T cells are being developed against many tumor cell targets. While tumor cell factors other than target expression level appear to play a role in determining the efficacy of CD3 bsAb, the identity of such factors remains largely unknown. Using a co-culture system of primary human T cells and B lymphoma cell lines, we demonstrate a range of sensitivities to CD20xCD3 bsAb that is independent of CD20 surface expression. To identify gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The authors also noted that despite depletion of exogenous BAM factors and sgRNAs for endogenous activation after transient transfection, endogenously activated factor genes remained high, suggesting sustained epigenetic remodeling of the targeted genomic loci achieved by the CRISPRa approach. This was further supported by chromatin immunoprecipitation (ChIP) qPCR data showing 61 Sensitivity to CD3 bispecific antibody JeKo-1 cells SAM hSAM Positive CD3 bispecific antibodymediated T cell killing Dukhovny 63 Protective host factors against zika virus Huh7 cells SAM hSAM Positive Resistance to zika virus infection Gilbert 30 Sensitivity to cholera/diphtheria toxin K562 cells SunTag Custom Positive Cholera/diphtheria-induced toxicity and death Konermann 55 Resistance to vemurafenib A375 cells SAM hSAM Positive Cell survival after treatment with vemurafenib Sanson 57 Resistance to vemurafenib A375 cells dCas9-VP64 Calabrese Positive Cell survival after treatment with vemurafenib Gilbert 30 Modulator of cell growth rate K562 cells SunTag Custom Negative Growth inhibition and depletion Horlbeck 56 Modulator significant enrichment in H3K27ac and H3k4me3 surrounding the promoter sequences of Brn2 and Ascl1 locimarkers of histone H3 modifications, not observed in BAM factor transgene overexpression.…”
Section: Cell-type Conversion Using Crispramentioning
confidence: 68%
See 1 more Smart Citation
“…The authors also noted that despite depletion of exogenous BAM factors and sgRNAs for endogenous activation after transient transfection, endogenously activated factor genes remained high, suggesting sustained epigenetic remodeling of the targeted genomic loci achieved by the CRISPRa approach. This was further supported by chromatin immunoprecipitation (ChIP) qPCR data showing 61 Sensitivity to CD3 bispecific antibody JeKo-1 cells SAM hSAM Positive CD3 bispecific antibodymediated T cell killing Dukhovny 63 Protective host factors against zika virus Huh7 cells SAM hSAM Positive Resistance to zika virus infection Gilbert 30 Sensitivity to cholera/diphtheria toxin K562 cells SunTag Custom Positive Cholera/diphtheria-induced toxicity and death Konermann 55 Resistance to vemurafenib A375 cells SAM hSAM Positive Cell survival after treatment with vemurafenib Sanson 57 Resistance to vemurafenib A375 cells dCas9-VP64 Calabrese Positive Cell survival after treatment with vemurafenib Gilbert 30 Modulator of cell growth rate K562 cells SunTag Custom Negative Growth inhibition and depletion Horlbeck 56 Modulator significant enrichment in H3K27ac and H3k4me3 surrounding the promoter sequences of Brn2 and Ascl1 locimarkers of histone H3 modifications, not observed in BAM factor transgene overexpression.…”
Section: Cell-type Conversion Using Crispramentioning
confidence: 68%
“…The majority of published CRISPRa screens utilized positive selection strategies, identifying perturbations that confer resistance to selected drugs, 55,57,61 toxins, 30,62 and pathogen infection 63 in resistant cell populations. Results from these positive selection screens all report the discovery of novel genes whose upregulation resulted in rescue from cell death in their respective studies.…”
Section: Genetic Screens Using Crispra Platformsmentioning
confidence: 99%
“…Based on our above appreciation for the heterogenous involvement of various CD3 subunits in T cell function and disease, targeting other CD3 subunits could be used to fine-tune desired T cell recruitment with BiTEs. BiTE efficacy is in part limited by specific tumor cell phenotypes, such as the expression of sialophorin which limits T cell to tumor cell adhesion ( 89 ), and by similar side effects of CRS and neurotoxicity observed in CAR Therapy ( 90 , 91 ). One study also identified a polymorphism in the CD3ζ chain (SNP rs2949655) that correlated with reduced cytotoxicity in response to BiTE treatment ( 92 ), demonstrating how CD3 mutational profiling could be used to help guide personalized treatment approaches targeting this pathway.…”
Section: T Cell Receptor Complexmentioning
confidence: 99%
“…Accordingly, the ESRRAi treatment upregulated genes involved in antigen presentation (Fig S5D ; Since increased MHC-I antigen presentation in tumors enhances the ability of T-cells to kill cancer cells (67,79), we hypothesized that ESRRAi would enhance tumor killing by T cells. We tested this using published CRISPR screens that co-culture cancer cells with T-cells to identify which gene knockouts in cancer cells enhance their T-cell-mediated killing (67,(80)(81)(82)(83). ESRRA KO potentiated the killing of cancer cells by both patient-derived and engineered effector T-cells in various experimental and cell-line contexts (Fig 3C).…”
Section: Inhibition Of Esrra (Esrrai) Stimulates Anti-tumor Immunitymentioning
confidence: 99%